On representation and weighted utilitarian representation of preference orders on finite streams - Tapan Mitra; Mahmut Kemal Ozbek (Cornell University, Center for Analytical Economics (CAE), 2010)
In this paper we re-examine the axiomatic basis of the key result on weighted utilitarian representation of preference orders on finite utility streams. We show that a preference order satisfying the axioms of Minimal Individual Symmetry, Invariance and Strong Pareto need not have a representation, and thus in particular a weighted utilitarian representation. The example establishing this result might also be of interest for the literature on the representation of preference orders. We then establish that whenever a preference order satisfying the axioms of Minimal Individual Symmetry, Invariance and Weak Pareto has a representation, it also has a weighted utilitarian representation. Our approach helps us to view the available results on the weighted utilitarian representation theorem from a different perspective.
Keywords: D60; D70; D90; 330; Minimal Individual Symmetry Axiom; Invariance Axiom; Pareto Axiom; Representation of Preference Orders; Weighted Utilitarian Representation; Decomposition of Irrationals